Metode Pirolisis Untuk Penanganan Sampah Perkotaan Sebagai Penghasil Bahan Bakar Alternatif - Wijayanti, Widya; Sasongko, Mega Nur; Meidiana, Christia; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
The research on the processing of organic municipal waste conversion has been done by using pyrolysis method. The research aims to gain an alternatif fuels and to minimize the landfill space. In the pyrolysis process, it was investigated the char formation as solid fuel as well as its heating value. The char formation was determined by the change of mass and volume of waste for minimizing landfill area.The waste compositions were obtained by surveying the 10 families during 10 days and then it was made the waste spesimens as the pyrolysis feedstocks. The pyrolysis processes were operated in range temperature 200oC to 400oC. Then, the char formations as pyrolysis products were tested by using bomb calorimeter to qualify the heating value of the products. The results showed that the waste was able to be a solid fuel due to the quality of its heating value. The increasing of the heating value could reach 150% from unpyrolyzed waste to pyrolyzed one. In addition, the pyrolysis method was able to significantly minimize the volume of waste, so that it has a potential way to overcome the need of a large landfil area in which it could reduce up to 50% in mass and 85% in volume. In waste pyrolysis method, it was only needed 2 hours operating process and low-temperature process (only up to 300oC). It did not require require a high-operating temperature, therefore, the handling of municipal organic waste to save area landfill and produce alternative fuel could be done in short time and did not require great energy.Keywords: waste, conversion energy, alternatif fuels, pyrolysis